2020
DOI: 10.1111/and.13545
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different mathematical models to assess seasonal variations in the longevity of DNA integrity of cooled‐stored stallion sperm

Abstract: Dynamic assessment of sperm DNA fragmentation (SDF) has shown to give fuller understanding of stallion semen quality; however, there have been limited attempts to use this parameter to investigate seasonal changes in productive functions. The aims of this study were to: (a) establish a reliable mathematical model to describe the longevity of cooled‐stored sperm DNA integrity; (b) to examine the effect of seasonal variations on SDF. Ejaculates were cooled to 5°C, and SDF was analysed after 0, 6 and 24 hr of sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
(91 reference statements)
0
1
0
Order By: Relevance
“…The effect of season on stallion reproduction has not been clearly established. Some authors reported that the non‐breeding season impairs endocrine profiles (Dhakal et al., 2011), number of Sertoli cells (Johnson, Varner, Tatum, & Scrutchfield, 1991), sexual behaviour characteristics, such as number of mounts per ejaculation and reaction time in the presence of an oestrous mare (Clay & Clay, 1992; Johnson, 1991; Picket, Faulkner, & Voss, 1975; Picket & Voss, 1972), and semen quality including semen volume, sperm concentration, total sperm number (Clay & Clay, 1992; Johnson, 1991; Picket et al, 1975; Picket & Voss, 1972), sperm kinetics (Jasko et al, 1991), total sperm number with progressive motility (Greiser, Sieme, Martinsson, & Distl, 2020), DNA fragmentation (Ortiz et al., 2020) and production of reactive oxygen species (Mislei, Bucci, Malama, Bollwein, & Mari, 2020). Other studies revealed lower DNA fragmentation and low intracellular calcium level, and higher total motility, viability (Wach‐Gygax et al., 2017) and progressive motility in the non‐breeding season (Greiser et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The effect of season on stallion reproduction has not been clearly established. Some authors reported that the non‐breeding season impairs endocrine profiles (Dhakal et al., 2011), number of Sertoli cells (Johnson, Varner, Tatum, & Scrutchfield, 1991), sexual behaviour characteristics, such as number of mounts per ejaculation and reaction time in the presence of an oestrous mare (Clay & Clay, 1992; Johnson, 1991; Picket, Faulkner, & Voss, 1975; Picket & Voss, 1972), and semen quality including semen volume, sperm concentration, total sperm number (Clay & Clay, 1992; Johnson, 1991; Picket et al, 1975; Picket & Voss, 1972), sperm kinetics (Jasko et al, 1991), total sperm number with progressive motility (Greiser, Sieme, Martinsson, & Distl, 2020), DNA fragmentation (Ortiz et al., 2020) and production of reactive oxygen species (Mislei, Bucci, Malama, Bollwein, & Mari, 2020). Other studies revealed lower DNA fragmentation and low intracellular calcium level, and higher total motility, viability (Wach‐Gygax et al., 2017) and progressive motility in the non‐breeding season (Greiser et al., 2020).…”
Section: Introductionmentioning
confidence: 99%